2010
DOI: 10.4172/jaa.1000024
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir/ritonavir + tenofovir Dual Therapy versus Lopinavir/ritonavir-Based Triple Therapy in HIV-Infected Antiretroviral Naïve Subjects: The Kalead Study

Abstract: With reference to the clinical need for simple, potent and safe antiretroviral regimens, Lopinavir/ ritonavir + tenofovir (LPV/r+TDF) two-drug initial regimen was studied for efficacy and safety in HIV-infected patients. Methods: Kalead was a prospective, randomized, open-label, 72-week trial comparing LPV/r+TDF versus LPV/r + two (non-TDF) NRTIs in HIV-infected adults with HIV-RNA >400 copies/mL and any CD4 count. Primary endpoint was the proportion of subjects with HIV-RNA <50 copies/mL at week 72. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Four randomized, non-inferiority trials were identified of NRTI-inclusive 2DRs in the treatment-naïve population ( Table 1) [10][11][12][13][14]. A small study of (lopinavir/ritonavir) LPV/ r ?…”
Section: Nrti Inclusivementioning
confidence: 99%
“…Four randomized, non-inferiority trials were identified of NRTI-inclusive 2DRs in the treatment-naïve population ( Table 1) [10][11][12][13][14]. A small study of (lopinavir/ritonavir) LPV/ r ?…”
Section: Nrti Inclusivementioning
confidence: 99%
“…A post hoc analysis also showed no difference in virological efficacy with respect to the choice of dual NRTI backbone and pre‐treatment CD4 cell count (<200 cells/ μ L) . A study comparing tenofovir‐DF and lopinavir/r to two NRTIs and lopinavir/r failed to demonstrate non‐inferiority of the dual‐therapy arm compared with a standard triple‐therapy combination but numbers were small and the response rates were numerically similar at 51% and 53%, respectively . As lopinavir/r is no longer among the first‐recommended PIs, the dual combination with lamivudine, as used in GARDEL study, has not been considered as an alternative first‐line regimen.…”
Section: What To Startmentioning
confidence: 99%
“…There is no cure to AIDS, a chronic illness [72] but can be a manageable chronic illness when treated with antiretroviral related therapies. There are several adverse side effects with those modes of treatment.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%